2022
DOI: 10.1093/jnen/nlac042
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb Amyloid-β Correlates With Brain Thal Amyloid Phase and Severity of Cognitive Impairment

Abstract: The Alzheimer disease (AD) neuropathological hallmarks amyloid β (Aβ) and tau neurofibrillary (NF) pathology have been reported in the olfactory bulb (OB) in aging and in different neurodegenerative diseases, which coincides with frequently reported olfactory dysfunction in these conditions. To better understand when the OB is affected in relation to the hierarchical progression of Aβ throughout the brain and whether OB pathology might be an indicator of AD severity, we assessed the presence of OB Aβ and tau N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Our studies find that even in patients predisposed to AD due to a genetic mutation of PS1 there is evidence of viral infection in the OB suggesting that viral infection and inflammatory response in the OT are part of the etiology of the disease. Taken together with a parallel body of literature indicating that early AD is characterized by smell loss 1-3 , amyloid deposition in the olfactory epithelium (OE), and olfactory sensory neuron (OSN) dysfunction 4, 5 , our study raises the possibility that viral infection of the OB/OT accelerates AD. Because sniff-induced beta and theta-coupled gamma oscillations generated in the OB are directionally coupled to the hippocampus 25-28 , smell loss would result in decreased hippocampal gamma oscillations that have been postulated to lead to neurodegeneration and cognitive decline 29-31 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our studies find that even in patients predisposed to AD due to a genetic mutation of PS1 there is evidence of viral infection in the OB suggesting that viral infection and inflammatory response in the OT are part of the etiology of the disease. Taken together with a parallel body of literature indicating that early AD is characterized by smell loss 1-3 , amyloid deposition in the olfactory epithelium (OE), and olfactory sensory neuron (OSN) dysfunction 4, 5 , our study raises the possibility that viral infection of the OB/OT accelerates AD. Because sniff-induced beta and theta-coupled gamma oscillations generated in the OB are directionally coupled to the hippocampus 25-28 , smell loss would result in decreased hippocampal gamma oscillations that have been postulated to lead to neurodegeneration and cognitive decline 29-31 .…”
Section: Discussionsupporting
confidence: 68%
“…Thus, it is essential to identify contributory pathological processes in early disease to prevent progression to dementia, disability, and death. An early process in AD, prior to clinical dementia, is a deficit in the sense of smell 1-3 accompanied by amyloid-beta (Aβ) deposition in the olfactory bulb (OB) 4, 5 . The OB receives olfactory input from olfactory sensory neurons in the olfactory epithelium (OE) 3, 6 then transmits olfactory information via the olfactory tract (OT) to the entorhinal cortex and hippocampus, brain regions essential for learning and memory that are affected in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Tau is believed to be the primary protein involved in the pathogenesis of olfactory impairment in AD. However, it has been reported that while Aβ pathology in the OB aligns with AD manifestation, Tau pathology in the OB is universally present in older adults and does not serve as an indicator of AD severity 37 . This suggests that Aβ deposition in the OB may serve as an early marker of AD onset.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5 × Familial AD mice, a model for AD pathology, display high levels of Aβ accumulation in the olfactory sensory network 36 . In humans, amyloid deposition directly affects olfactory regions in the brain, leading to olfactory impairment 37 . Autopsy studies on 536 cases examining OB neuropathology in AD cases showed Aβ accumulation in the OB starting from stage 0 of Tahl Aβ phase, progressing as they advance to stage 5 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation